Seroprevalence of transfusion-transmissible infections among family replacement donors and voluntary non-remunerated blood donors during the COVID-19 pandemic in sub Saharan Africa - Macoura Gadji; Youssou Bamar Gueye; David Motto; Saliou Diop (Mediterranean Journal of Hematology and Infectious Diseases)
Introduction : According to WHO,  regular, voluntary, unpaid blood donors are the safest group of donors, as they have the lowest prevalence of blood transmitted infections. However, family/replacement blood donors is widely used in sub Saharan Africa and this practice was exacerbated during the COVID 19 pandemic. This study aimed to compare the seroprevalence of infectious markers in family replacement blood donors and voluntary non-remunerated  blood donors during the COVID 19 pandemic in a country of sub Saharan Africa.